Donovanosis. Issue 6 (1st December 2002) - O'Farrell, N
Abstract : Donovanosis, a chronic cause of genital ulceration, has recently been the subject of renewed interest after a long period of relative obscurity. The causative organism, Calymmatobacterium granulomatis, has been cultured for the first time in many years and a polymerase chain reaction diagnostic using a colorimetric detection system has been developed. Phylogenetic analysis confirms close similarities with the genus Klebsiella and a proposal made that C granulomatis be reclassified as Klebsiella granulomatis comb nov . Azithromycin has emerged as the drug of choice and should be used if the diagnosis is confirmed or suspected. In donovanosis endemic areas, syndromic management protocols for genital ulceration may need to be adapted locally. A significant donovanosis epidemic was reported in Durban from 1988–97 but the current status of this epidemic is unclear. The donovanosis elimination programme among Aboriginals in Australia appears successful and is a model that could be adopted in other donovanosis endemic areas. Overall, the incidence of donovanosis seems to be decreasing. Increased attention would undoubtedly be paid to donovanosis if policy makers recognised more readily the importance of genital ulcers in fuelling the HIV epidemic.